MEMBUDAYAKAN NILAI-NILAI HAM DALAM RANGKA PENGUATAN PANCASILA DAN KEBHINEKAAN - Adoniati Meyria Widaningtyas H; Triyanto Triyanto (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2019)
Indonesia is a nation state which involves a series of various ethnic, reli- gious, racial, class, cultural and political views. It is a social capital for the magnitude of a nation. But unfortunately, lately this social capital with the increasing of intolerant attitudes from most people that have an impact on the increasing of social conflicts based on racial intolerance in many regions also penetrated educational environment should be free from the problems of racism and politics. To response, the internalization of the Pancasila values is impSortant to do back in order to build the na- tion’s character. 45 values of Pancasila need to be revived and contextu- alisation with the present of situation as well as universal human rights values. On the other hand, the attitude and actions of tolerance for diver- sity of the Indonesian nation today is not enough to just set in the written rules and to enforced, but must be internalized as the basis for rebuilding the nation’s character. The values of universal human rights which in- cluded a tribute to human dignity, equality, non-discrimination, inclu- sion and tolerance in this case can strengthen revitalization nationalities to movement directed at strengthening the resilience of communities and “bhineka” nations to efforts nihilisasi from outsiders on positive cultural values of Indonesia nation. The internalisation of human rights values can be done with the civilizing in which the efforts of recognition and understanding, then learning, implementation, habituation, accultura- tion and imitation that conducted together by all elements of society in the life of the nation. The internalizing process of human rights values can also be done through the development of alternative methods is one of them forming a role model that will give more results and significant impact. That efforts are very strategic to start with education because ed- ucation is a vehicle for character development through cognitive, affective and psychomotor.